Investigasi Regulasi Diri (Self Regulation) dan Kualitas Hidup (Quality of Life) pada Anak Usia 4-6 Tahun di PAUD Hubbullah - Syalwatul Aisyi; Abd Rosyid (STAI Al Mujtama Pamekasan, 2025)
This study investigation the constructs of self regulation and quality of life in early childhood at PAUD Hubbullah. The primary objective of this research is to determine how children’s self regulatory capabilites influence various dimensions of their quality of life, including emotional management, impuls control, and resistance to tantrums. Additionally, the study examines how aspects of a child's quality of life such as parenting practices, interactions with peers, and engagement with the surrounding community affect behavioral outcomes. The research employs a descriptive qualitative methodology, utilizing observational and interview techniques for data collection. The data sources comprise both primary and secondary materials. The findings indicate that children who demonstrate well developed self regulation also exhibit stronger academic performance. Similarly, children who experience a high quality of life tend to show both effective self regulation and commendable academic abilites. Trough self regulation, children are able to exercise self control and adhere to established norms and rules. Morever, a supportive quality of life facilitates behavioral regulation and allows for better monitoring of developmental progress. In conclusion, both self regulation and quality of life are fundamental for the child’s future development and overall well being.